An assessment of a massively parallel sequencing approach for the identification of individuals from mass graves of the Spanish Civil War (1936–1939). Issue 21 (5th September 2016) - Calafell, Francesc; Anglada, Roger; Bonet, Núria; González‐Ruiz, Mercedes; Prats‐Muñoz, Gemma; Rasal, Raquel; Lalueza‐Fox, Carles; Bertranpetit, Jaume; Malgosa, Assumpció; Casals, Ferran
Abstract : Next‐generation sequencing technologies have opened new opportunities in forensic genetics. Here, we assess the applicability and performance of the MiSeq FGx™ & ForenSeq™ DNA Signature Prep Kit (Illumina) for the identification of individuals from the mass graves of the Spanish Civil War (1936–1939). The main limitations for individual identification are the low number of possible first‐degree living relatives and the high levels of DNA degradation reported in previous studies. Massively parallel sequencing technologies enabling the analysis of hundreds of regions and prioritizing short length amplicons constitute a promising tool for this kind of approaches. In this study, we first explore the power of this new technology to detect first‐ and second‐degree kinship given different scenarios of DNA degradation. Second, we specifically assess its performance in a set of low DNA input samples previously analyzed with CE technologies. We conclude that this methodology will allow identification of up to second‐degree relatives, even in situations with low sequencing performance and important levels of allele drop‐out; it is thus a technology that resolves previous drawbacks and that will allow a successful approximation to the identification of remains.